Simulasi dan Uji Fungsional Dashboard Monitoring Kualitas Air Kolam Ikan Berbasis MQTT - Anjelita Trully Carolina Losung; Riyandy Kumalaka; Yuscar Agsbastian; Maureen Langie; Marike Kondoj (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Water quality plays a crucial role in fish farming because changes in pH, temperature, water content, turbidity, and total dissolved solids (TDS) can affect the condition and health of fish. Manual monitoring still has limitations because data is not available continuously, and early warnings are difficult to provide when water conditions begin to exceed safe limits. This study aims to develop and functionally test an Internet of Things (IoT)-based fish pond water quality monitoring dashboard using the MQTT protocol. Testing was conducted in a simulated environment to evaluate data transmission, data storage, dashboard visualization, status classification, and alert logging. Test results show that the system is capable of receiving and storing 204 sensor data records and generating 248 alert data entries in the `alert_log` table. The dashboard successfully displays the statuses NORMAL, WARNING, DANGER, and CRITICAL in accordance with the defined threshold rules. This research contributes to the development of an initial prototype of a simulation-based water quality monitoring system that can be used to verify data flow integration and dashboard responses before implementation on real devices. This research is not intended as a validation of physical sensors or an evaluation of field network performance, but rather as an initial test of the simulation system’s functionality.